Exploring heterogeneity among backpackers in hostels - Brochado, A.; Rita, P. (Current Issues in Tourism, 2018)
This study’s goal was to validate the core dimensions of hostel service quality and to test whether each dimension has a different impact on behavioural intentions across guest segments defined by age, gender and nationality. This research targeted guests staying at Lisbon hostels (N?=?313). Both covariance-based structural equation modelling (SEM) and variance-based SEM were used to meet this study’s exploratory and confirmatory objectives. The results confirm that service quality in this sector is a multidimensional construct comprising four core dimensions: quality of staff, social atmosphere, hostel tangibles and city connection. These four aspects are relevant when explaining levels of satisfaction, recommendation and revisiting intentions. Moreover, these dimensions allow the identification of differences across market segments in regards to responses to marketing outcomes, thus providing useful insights into how best to meet guests’ needs.